Toraja local wisdom e-comics with a STEM approach to improve mathematical concept understanding and problem-solving skills - Lolang, Enos; Putra Pratama, Muh. (Jurnal Inovasi Teknologi Pendidikan, 2026)
Mathematics learning is often perceived as difficult due to its abstract nature and the lack of contextual media that connect concepts to students’ real-life experiences. However, Toraja culture contains various elements embedded with mathematical principles, such as symmetrical carving patterns, the geometric structure of Tongkonan, and traditional calculations in social practices. These cultural aspects can serve as meaningful visual and narrative contexts to support conceptual understanding. This study aims to develop a Toraja Local Wisdom E-Comic based on the STEM approach to enhance students’ conceptual understanding and problem-solving skills in mathematics. The research employs the ADDIE model, consisting of analysis, design, and development stages. The e-comic is presented as an interactive digital medium integrating Toraja cultural stories with mathematical concepts and STEM-based explanations. Validation was conducted by material and media experts, while practicality testing involved students as users. Data were analysed using descriptive, quantitative, and qualitative methods. The results indicate high validity, with average scores of 4.72 for material aspects and 4.65 for media aspects. The practicality test yielded an average score of 4.66, indicating that the e-comic is easy to use, engaging, and effective in facilitating understanding through cultural context. Therefore, the e-comic is considered valid and practical, with strong potential to improve mathematics learning outcomes. Further research will examine its effectiveness in classroom implementation.